## f(x)+3

### The expression “f(x) + 3” represents the sum of the function f(x) and 3

The expression “f(x) + 3” represents the sum of the function f(x) and 3. In other words, you would take any input x, evaluate the function f(x), and then add 3 to the result.

For example, let’s say we have a function f(x) = 2x – 1. If we want to evaluate f(x) + 3 when x = 4, we substitute 4 into the function:

f(4) = 2(4) – 1 = 8 – 1 = 7

Then we add 3 to the result:

f(4) + 3 = 7 + 3 = 10

So, in this case, f(4) + 3 equals 10.

##### More Answers:

Understanding Quadratic Functions | x² + 5 – Analyzing the Polynomial, Graph, and RootsUnderstanding the Expression f(x-5)+4 | Step-by-Step Breakdown and Analysis

Step-by-Step Explanation of the Algebraic Expression f(x+5)-4

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded